Atypical primary biliary cholangitis results in vanishing bile duct syndrome with cutaneous xanthomas: a case report - Yuebo Jia; Lin Liu; Baocheng Deng; Yu Huang; Jiaqi Zhao; Guang Bai (BMC, 2022)
Abstract Background Vanishing bile duct syndrome (VBDS) is a rare but potentially severe acquired chronic cholestatic liver disease. Bile duct deficiency is a reduction of bile ducts in the liver, which can eventually lead to cholestatic liver disease and progress to biliary cirrhosis. Primary biliary cholangitis (PBC) is one of the causes of bile duct deficiency. In addition, 75% of PBC patients may have dyslipidemia, and in case of secondary dyslipidemia, cutaneous xanthomas may occur. Case summary A 49-year-old woman was admitted with jaundice and multiple subcutaneous nodules. She received diagnosis of autoimmune liver disease 2 years before. Although she was treated with liver-protecting drugs, such as Essentiale and ursodeoxycholic acid, jaundice occurred repeatedly, and the color of her skin was becoming darker and more yellow. Conclusion This case highlights that the positivity of ANA that in PBC have a well diagnostic and prognostic significance and antinuclear antibodies giving the 'multiple nuclear dots' or the 'rim-like/membranous' pattern scan ca diagnose primary biliary cirrhosis accurately. Since the liver biopsy of PBC alone may not be sufficient to establish the diagnosis, serum antibodies should also be examined. PBC can also lead to intrahepatic cholestasis, which can cause dyslipidemia and cutaneous xanthomas.